Fertility-conservation combined therapy with hysteroscopic resection and oral progesterone for local early stage endometrial carcinoma in young women - Wang, Qing (Int J Clin Exp Med, 2015)
Objects: This paper explored the suitable population for the combined therapy of hysteroscopic resection and oral megestrol acetate (MA) to treat local stage I endometrial cancer. Therapeutic effectiveness, safety, as well as pregnancy rate and relapse rate after treatment were also examined. The aim was to provide guidance for the treating similar cases in the future. Methods: This perspective study analyzed the clinical data of early stage endometrial cancer patients who have received combined therapy of hysteroscopic resection of local endometrial lesion and oral administration of MA at the Obstetrics and Gynecology Hospital of Fudan University, Shanghai. Results: A total of six patients met the entry criteria and were enrolled into the trial. All of them achieved a pathologic complete response to hysteroscopic resection of local lesion combined with oral administration of MA for 3 months to 6 months. Among the patients, three became pregnant after natural conception and had healthy infants delivered vaginally at full term without assistance. No relapse occurred in the follow-up study over 48.5 months on average. Conclusions: In early-stage endometrial cancer, young patients who had already given birth demand may receive hysteroscopic resection combined with oral administration of MA as conservative treatment. The patients can consider natural conception after complete remission, but a close follow-up was crucial to ensuring that the patients were free from other factors affecting childbearing ability.